Regional Economic Outlook, October 2020, Western Hemisphere : Pandemic Persistence Clouds the Recovery. (International Monetary Fund, 2020)
The pandemic continues to spread in Latin America and the Caribbean (LAC), but economic activity is picking up. After a deep contraction in April, activity started recovering in May, as lockdowns were gradually eased, consumers and firms adapted to social distancing, some countries introduced sizable policy support, and global activity strengthened.